Innovation in the Processing of Livestock and Seaweed Products Using a Food Chemistry Approach in Ampekale Village - Nudia Tuljannah; Siti Yasya Ey Fathanah; Risqah Amaliah Kasman; Kartini J; winda (ITEKES Permata Ilmu Maros, 2025)
The availability of functional food that is safe, nutritious, and has added value is a strategic issue in sustainable development. Ampekale Village in Maros Regency is a center for seaweed cultivation, yet local communities lack the skills to process their harvest into high-value food products. The main problem identified is the limited knowledge and technical capacity to utilize seaweed and local livestock as raw materials for modern food products such as nuggets and yogurt. This community engagement program aimed to enhance the capacity and self-reliance of the Seaweed Farmers Cooperative Group through the application of food chemistry and applied animal science. The methods used included interactive lectures, discussions, and hands-on demonstrations, involving 35 participants consisting of micro-entrepreneurs and housewives. Evaluation was conducted through a Likert-scale questionnaire and direct observation. The results indicated a significant improvement in participants’ understanding of functional food concepts, food safety, and technical skills in processing and packaging products. Participants also expressed a strong interest in developing independent businesses, with some already beginning small-scale production at home. This program successfully integrated scientific knowledge with appropriate technology in a practical manner and had a positive impact on the economic empowerment of coastal communities. The initiative also shows strong potential for sustainability and replication in other coastal areas with similar resource characteristics.